2020
DOI: 10.1186/s13046-020-01742-4
|View full text |Cite|
|
Sign up to set email alerts
|

Gallbladder cancer-associated fibroblasts promote vasculogenic mimicry formation and tumor growth in gallbladder cancer via upregulating the expression of NOX4, a poor prognosis factor, through IL-6-JAK-STAT3 signal pathway

Abstract: Background Cancer-associated fibroblasts (CAFs) and vasculogenic mimicry (VM) play important roles in the occurrence and development of tumors. However, the relationship between CAFs and VM formation, especially in gallbladder cancer (GBC) has not been clarified. In this study, we investigated whether gallbladder CAFs (GCAFs) can promote VM formation and tumor growth and explored the underlying molecular mechanism. Methods A co-cultu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 57 publications
0
37
0
Order By: Relevance
“…JAK2-STAT3 pathway is one of the most important cell signal transduction pathways. Some studies have shown that JAK-STAT3 pathway plays a key role in endothelial cell activation and can increase the cell proliferation and adhesion in endothelial cells (26,27). For example, activation of JAK-STAT3 pathway is essential for IL-6-mediated proinflammatory response of HUVECs (28).…”
Section: Discussionmentioning
confidence: 99%
“…JAK2-STAT3 pathway is one of the most important cell signal transduction pathways. Some studies have shown that JAK-STAT3 pathway plays a key role in endothelial cell activation and can increase the cell proliferation and adhesion in endothelial cells (26,27). For example, activation of JAK-STAT3 pathway is essential for IL-6-mediated proinflammatory response of HUVECs (28).…”
Section: Discussionmentioning
confidence: 99%
“…For example, NFAT1-regulated IL6 signaling contributes to the aggressive phenotypes of glioma ( 23 ). Cancer-associated fibroblasts promote gallbladder cancer growth via activation of the IL6-JAK/STAT3 signal pathway ( 24 ). Ovarian carcinoma-associated mesenchymal stem cells can activate the tumor cell stemness via activating IL6/STAT3 signaling ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, NFAT1regulated IL6 signaling contributes to the aggressive phenotypes of glioma [23]. Cancer-associated broblasts promote gallbladder cancer growth via activation of the IL6-JAK/STAT3 signal pathway [24]. Ovarian carcinoma-associated mesenchymal stem cells can activate the tumor cell stemness via activating IL6/STAT3 signaling [25].…”
Section: Discussionmentioning
confidence: 99%